Distinct Clinical and Genetic Findings in Iranian Patients With Glycogen Storage Disease Type 3. Issue 4 (June 2018) - Nazari, Ferdos; Sinaei, Farnaz; Nilipour, Yalda; Petit, François; Oveisgharan, Shahram; Nassiri-Toosi, Mohsen; Razzaghy-Azar, Maryam; Mahmoudi, Mahdi; Nafissi, Shahriar
Abstract: Objectives: Glycogen storage disease type 3 (GSD-III) is a rare inherited metabolic disorder caused by glycogen debranching enzyme deficiency. Various pathogenic mutations of the AGL gene lead to abnormal accumulation of glycogen in liver, skeletal, and cardiac muscles. Here, we report distinct clinical and genetic data of Iranian patients with GSD-III. Methods: Clinical and laboratory data of 5 patients with GSD-III were recorded. Genetic investigation was performed to identify the causative mutations. Results: Three patients had typical liver involvement in childhood and one was diagnosed 2 years after liver transplantation for cirrhosis of unknown etiology. Four patients had vacuolar myopathy with glycogen excess in muscle biopsy. All patients had novel homozygous mutations of the AGL gene namely c.378T>A, c.3295T>C, c.3777G>A, c.2002-2A>G, and c.1183C>T. Conclusions: This is the first comprehensive report of patients with GSD-III in Iran with 2 uncommon clinical presentations and 5 novel mutations in the AGL gene.